Analisis Kinerja On-Path Caching Dan Off-Path Caching Pada Information-Centric Networking - Muhamad Rizka Maulana; Achmad Basuki; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The massively increasing Internet traffic is not supported by the current Internet architecture which is still based on host-centric communication. Information-centric networking (ICN) paradigm has been proposed to resolve that problem with content-centric communication. Some ICN architectures have been proposed, such as CCN, DONA, and NetInf. Those proposed architectures generally have three main concepts, which are publish-subscribe operation, in-network caching, and content-oriented security. In-network caching plays a very important role in ICN paradigm. It can improve network performance by saving content in caches that are spread in the network. This research aims to compare on-path caching and off-path caching strategies using Biznet topology on Icarus simulator. The result shows that off-path caching has 12.45% higher cache hit ratio than on-path caching, and on-path caching has 63.14% lower link load and 42,07% lower latency than off-path caching. In addition to that, it is worth noted that bigger cache capacity and Î± value results in higher cache hit ratio, lower link load, and lower latency.